Phosphorescence enhancement triggered by pi stacking in solid-state [Cu(N-N)(P-P)]BF4 complexes - Zhang, Liming (Langmuir : the ACS journal of surfaces and colloids, 2009)
In this article, we report a phosphorescence enhancement phenomenon of [Cu(N-N)(P-P)]BF4 complexes in the solid state. The phosphorescence enhancement phenomenon is composed of three features: (1) an obvious emission blue shift, (2) a greatly enhanced photoluminescence quantum yield, and (3) a longer excited-state lifetime. Systematic analyses prove that the main cause of this phenomenon is nonradiative process suppression triggered by the pi stacking between [Cu(N-N)(P-P)]BF4 molecules. The phosphorescence enhancement widely exists in [Cu(N-N)(P-P)]BF4 complexes because of the pi surfaces in their diimine ligands